Decision Support System for Internet Service Provider Selection with Weight Product Method - Noviandi Noviandi; Ray Fadly Franata; Ervan Jefferson Bany; Septyanto Harry Nugroho (Universitas Islam Kuantan Singingi, 2022)
People's need for internet connection is a must nowadays, as everyone surely performs all activities through the internet. All activities require internet connection, be it work, lectures, gaming, household payments, shopping and many other activities that are done online. However, because people still rely on the experiences of other users when choosing Internet providers, it is difficult to find a fiber Internet service provider whose quality of service meets one's needs. The decision support system can help people choose an Internet service provider efficiently. The decision support system for fiber optic Internet service provider selection uses the weighted product method, which is one of the methods in the decision support system. The weighted product method is considered suitable to determine the best fiber optic internet service provider in North Jakarta with the appropriate weighting. The stages of the weighted product method include determining the priority value of each criterion, calculating the weight of the criterion, calculating the vector Si, calculating the vector Vi, and making the decision based on the results of the vector Vi calculations. The largest Vi value is the best alternative option. The results of this study are proven to be able to provide an objective alternative for choosing the best Internet service provider in the North Jakarta area.